1998
DOI: 10.2323/jgam.44.297
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between methanogenic and sulfate-reducing microorganisms during dechlorination of a high concentration of tetrachloroethylene.

Abstract: Tetrachloroethylene (PCE) is a chlorinated aliphatic compound essentially used as a degreasing and drycleaning solvent. It is commonly found as a groundwater contaminant and because of its carcinogenic properties is considered a pollutant. Biotransformation of PCE in ethane or ethylene has been studied by many researchers at low concentrations under strict anaerobic conditions (De Bruin et al., 1992;Freedman and Gossett, 1989).The dechlorination process was observed in methanogenic, acetogenic, or sulfate-redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
(19 reference statements)
0
21
0
2
Order By: Relevance
“…SRB are an important group of morphologically very closely related anaerobic microorganisms which have been shown capable of dehalogenation of different chlorinated solvents including TCE, PCE, DCE and also degradation of petroleum BTEX compounds by various researchers (7,9,10). Gu et al recently reported microbially mediated iron-sulfide precipitate in ZVI columns (25).…”
Section: E Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRB are an important group of morphologically very closely related anaerobic microorganisms which have been shown capable of dehalogenation of different chlorinated solvents including TCE, PCE, DCE and also degradation of petroleum BTEX compounds by various researchers (7,9,10). Gu et al recently reported microbially mediated iron-sulfide precipitate in ZVI columns (25).…”
Section: E Results and Discussionmentioning
confidence: 99%
“…Thus, our finding that SRB are the predominant organisms in the ZVI is in accordance with the subsurface redox chemistry at the site. SRB are an important group of morphologically closely related anaerobic microorganisms which have been shown capable of dehalogenation of different chlorinated solvents including TCE, PCE, DCE and also degradation of petroleum BTEX compounds by various researchers (7,9,10). SRB reduce subsurface sulfate and other sulfur compounds to sulfide, which can be coupled to oxidation of the ZVI forming iron sulfide mineral.…”
Section: Section Rv Results and Discussionmentioning
confidence: 99%
“…Inhibition of dehalogenation under sulfate-reducing conditions has been attributed to competition between sulfate and chlorinated compounds for electron donor (Alder et al 1993). Conflicting reports exist as to the effect of sulfate reduction on microbial dechlorination, from lack of inhibition (Bagley and Gossett 1990;DeWeerd et al 1991;Hoelen and Reinhard 2004;Pavlostathis and Zhuang 1991), to partial inhibition (Aulenta et al 2008;Cabirol et al 1998), or to complete inhibition (Nelson et al 2002). Considering the significant role molecular hydrogen (H 2 ) plays as a terminal electron donor in microbial reductive dechlorination reactions (Aulenta et al 2008;DiStefano et al 1992;Fennell et al 1997;Kassenga and Pardue 2006;Löffler et al 1999;Smatlak et al 1996;Yang and McCarty 1998), the outcome of competition among various microbial groups for H 2 utilization at relatively low H 2 concentrations may be explained by the fact that the H 2 threshold of dechlorinating bacteria (\0.3-2 nM) is significantly lower than that of hydrogenotrophic methanogens (5-95 nM), and similar to that of hydrogenotrophic sulfate reducers (1-4 nM) (Aulenta et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Provided that appropriate environmental conditions exist, chlorinated aliphatic and aromatic hydrocarbons undergo reductive dechlorination in sulfatereducing environments with different electron donors (Alder et al 1993;Aulenta et al 2008;Bagley and Gossett 1990;Cabirol et al 1998;De Best et al 1997a, b;Häggblom and Young 1990;Kennedy et al 2006;Ndon et al 2000;Palekar et al 2003;Pavlostathis and Zhuang 1991;Prytula and Pavlostathis 1996;Sonier et al 1994). Degradation of chlorinated aromatic compounds coupled to sulfate reduction yields higher free energy than degradation coupled to methane production (Häggblom and Young 1995).…”
Section: Introductionmentioning
confidence: 94%
“…Various studies in the past have shown that sulfatereducing bacteria (for example, Desulfovibrio vulgaris, Desulfovibrio gigas, and Desulfovibrio desulfuricans) are able to metabolize substrates such as lactate to acetate, CO 2 , and H 2 when grown in the absence of sulfate or in media with low sulfate concentrations, in syntrophic association with H 2 -consuming bacteria keeping the hydrogen partial pressure low (for example, Desulfovibrio vulgaris with Methanosarcina barkeri or Desulfovibrio fructosivorans with Methanospirillum hungatei [5,6,9,40]). It was also found that a few Desulfovibrio species can either utilize or produce hydrogen (mediated by reversible hydrogenases or two different hydrogenases) during the degradation of organic matter (for example, Desulfovibrio vulgaris, Desulfovibrio gigas, Desulfovibrio salexigens, and Desulfovibrio baculatus [20]).…”
Section: Discussionmentioning
confidence: 99%